Fractures and Chronic Recurrence are Commonly Associated with Ankle Sprains: a 5-year Population-level Cohort of Patients Seen in the U.S. Military Health System - Daniel I Rhon; Tina A Greenlee; Chad E Cook; Richard B Westrick; Jon A Umlauf; John J Fraser (International Journal of Sports Physical Therapy)
# Background